PENERAPAN LAYANAN BIMBINGAN KONSELING PAUD - Roudlotun Ni’mah; Farida Isroani; Muflihaini (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Counseling guidance services in children in PAUD as assistance provided to children in developing optimal aspects of development with the aim that children become responsible and independent in solving problems. The stages of the implementation of counseling guidance services in early childhood include planning, implementation, evaluation, and follow-up. This type of research is a type of field research or case study. And it's qualitatively deskritive. Data collection techniques are carried out by interviewing to find out the school's point of view on the implementation of counseling guidance services in early childhood education while additional data in the form of observation and documentation. The result of this study is the implementation of counseling guidance services in early childhood education n has been going well, which is illustrated from the planning that includes the identification of learners' problems through the child's personal data form. Implementation includes data collection, information, extension, placement and devaluation services. Evaluation includes conformity between the program and implementation, compliance with the program, obstacles, responses of children, teachers and parents and changes in progress in the provision of guidance also running as a whole. Follow-up includes other methods performed if an action that has been performed has not been successful. Counseling guidance services include nonprofessional counseling guidance services, because those who become counseling guidance teachers are classroom teachers appointed by the principal as BK teachers.